Dewatering of ionic liquids in a falling film evaporator - Wellner, Niels; Siebeneck, Karl; Ramunno, Monique; Wasserscheid, Peter; Scholl, Stephan (Chemie Ingenieur Technik, 2011)
Experimental investigations on the dewatering of ionic liquids (IL) in a single falling film evaporator were carried out. Depending on the process conditions, such as heating temperature and process pressure, a minimum water content of 0.2 wt-% (2000 ppm) was achieved using batch mode. Assuming that these water contents represent equilibrium state at constant temperatures and pressures, vapor pressure curves of different IL-water mixtures were obtained and from these the required heat for evaporation could be estimated. During the dewatering process viscosity was monitored online and proved to be a sufficient and reliable indicator for dewatering progress. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Dewatering; Falling film evaporator; Ionic liquids